Laboratory Hemostasis : A Practical Guide for Pathologists - Bennett, Sterling T.; Lehman, Christopher M.; Rodgers, George M. (Springer International Publishing : Imprint: Springer, 2015)
Coagulation testing is the basis for the diagnosis of bleeding and thrombotic disorders, as well as the mainstay of anticoagulant monitoring and management. This handbook provides practical information and guidance on topics relevant to directing a coagulation laboratory, filling a void in the literature. The book cites consensus recommendations of authoritative bodies whenever possible, and otherwise refers to reviews, chapters, and research articles from experts. Since the first edition, all chapters have been updated, and an entirely new chapter is included on pharmacogenomics and pharmacogenetics.   Laboratory Hemostasis: A Practical Guide for Pathologists will aid pathologists, clinical laboratory scientists, and other physicians serving as laboratory directors to understand and carry out their responsibilities. It will also assist residents and fellows in learning the basics of coagulation testing and serve as a useful day-to-day reference for coagulation laboratory supervisors, technologists, and technicians. Finally, clinicians may find aspects of the book helpful in understanding the role of the coagulation laboratory in patient evaluation and monitoring.